Composição bromatológica de silagem de aveia submetida à adubação nitrogenada e estádios fenológicos de ensilagem - Zamarchi, Gustavo (2013)
The silage is the most useful way of conserving forage for ruminants. The timing of the cut for silage should seek for a balance between productivity and nutritional value of forage, however, the process may occurs adequately when the plant presents appropriate characteristics, particularly regarding moisture content, and presents no resistance of fermentation stabilization. The overall objective was to evaluate the the effect of factors: particle size, nitrogen fertilization, growth stages and pre-wilting preceding the silage of white and black oat, to improve fermentation characteristics and nutritional value of this silage. Thus, two experiments were conducted, one at Federal Technological University of Paraná, Dois Vizinhos-PR, using white oat (Avena sativa L.) cultivar URS Guapa, developed in a randomized block design, with treatments distribution as a factorial (6x3), evaluating six doses of nitrogen: 0, 40, 80, 120, 160 and 200 kg ha-1 and three cutting stages for silage: early flowering, with and without pre-wilting and full flowering without pre-wilting. Another experiment was conducted in a private farm, at the municipality of Renascença-PR, using black oat (Avena strigosa S.) cultivar common, in a full randomized design, arranged in a factorial (3x2x2), evaluating three particle sizes: 5, 13, and 22 mm; two silage stages: early flowering and full flowering; and two operations: with and without pre-wilting. Both were conducted during the winter of 2011, being assessed the fermentation process and chemical composition of silage. The operation of pre-wilting increased the dry matter content (DM) in both studies, for white oat provided better preservation of crude protein (CP), while for black oat, provided the better silage fermentation conditions, reducing buffering capacity (BC) and pH, which ensured better preservation of the nutritional value of the forage, having lower levels of neutral (NDF) and acid (ADF) detergent fiber. Showed even higher levels of CP, in vitro digestibility of dry matter (IVDMD) and total digestible nutrients (TDN). The particle size influenced only the silage pH. With the advancing maturity, from the start to full flowering, there was a reduction in the levels of mineral matter (MM), ether extract, CP and IVDMD, in the second work it was also observed reduction in TDN and elevation in the levels of NDF and ADF. Nitrogen fertilization caused a linear reduction in pH and MM, and there was also a reduction in NDF and ADF and elevation in CP, both linearly.